Collaborative multimodal authoring of virtual worlds - Sá, Vítor (2011)
This work aims the creation of virtual worlds by working teams with resource to advanced interaction techniques, such as speech commands and gestures, as well as the resource to portable devices. The physical characteristics of virtual reality environments lead us to a different kind of user interfaces. However, we found some usefulness on the classic WIMP paradigm, which we also apply by using a PDA, in order to complement the interaction possibilities. In terms of application description we use the Virtual Reality Modeling Language. One of the main goals is the separation/combination of VRML files in order to allow the work to be cared out individually by the members of the team, and later combine the results to produce the global virtual world.